On obtaining exact estimates for the derivative of the error of spline interpolation - Korneichuk , N. P. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
Using new facts on the behavior of derivatives in spline interpolation, we give a proof for exact estimates of the error in approximating the first derivative.